On the Origin of Reality: How We Create Our Own World - Peter Verheyen (Current Perspective to Physical Science Research Vol. 2, 2023)
Consider the following: A scientist studying atoms, is a group of atoms studying themselves. A strange way of looking at reality. To understand, we have to travel through the world of the infinitesimal, governed by rules and laws, different from the ones we know from our classical world. We have to enter the world of information. Max Born created the measurement problem with his statistical interpretation of the quantum mechanical wave-function: the strange connection between the collapse of a quantum mechanical wavefunction and measurement, observation, interaction with the environment, with projection into a single concrete reality in a classical world. Where a measurement or observation creates the relevant past history, John Wheeler’s eye. The universe urges for an increase in entropy and information processing. This increase makes the universe a bustling place where life such as ours can arise. The biochemistry of all life we know, has an essential basic property as the sole islands in the known universe succeeding in keeping its own entropy low: life is capable of violating the second law of thermodynamics. Life manages to prevent equally distribution of matter and energy in which case all biochemical processes stop and life ends. Growing old and dying, for every solely living thing on Earth, means being not able anymore to keep its entropy low, leading to a malfunction in the biochemical machinery, failing fundamental processes, wear and ultimately death. Keeping its entropy low, is a basic property of life. Entropy describes a system on a microscopic level and is closely related to information, the Shannon entropy, combined to as Infotropy. They are 2 parts of the same coin, closely connected with the statistics governing the rules of the universe. An average human body contains about 7 octillion (a 7 with 27 zeros) atoms and they all ‘know’ exactly what to do and how to interact. Hidden webs of information guide the atoms and molecules in their biochemical reactions, while obeying the strange laws of quantum physics: every chemical and biochemical reaction depends on the interplay of electrons. This all is guided by communication between and information streams and exchange in the subsystems of the cellular machinery. The universe produced brains, so why can’t the universe itself be a giant super brain. All we call real is made up out of things which cannot be considered as real. Our senses are biochemical measuring instruments in our interaction with the environment. They don’t serve to reveal us reality but to help us to survive. Their information is interpreted in the brain as a ‘reality vital to life.’ The brain holds a mask in front of reality behind which the real world, the world of information and quanta lies concealed. The qubits, the quantum information that makes up the universe, do not signify anything concrete, but are transformed by biochemical projection and neural interpretation into apparent reality, as electrical circuits and software do in creating a 3D virtual reality. The deepest layer of reality consists out of information. Information is the building block of the universe, although a qubit is not a physical object but contains information about the physical object. Information is real and has to obey physical laws. Consciousness, emerging from the exchange of information via chemical and electrical signals, allowing life to have a notion or awareness of its environment, is the appearance of a world trough biochemical information projection and neural interpretation. The brain, the most complex piece of matter in the known universe, creates reality. Which brings us to the question: How can we possibly know what there is out there, if we ourselves, are locked up in complete darkness in a small box. Graphical Abstract: Saldesign.